B-cell Lymphoma 9 (BCL9) Gene Methylation as a Biomarker for Gastrointestinal Diseases and Gastric Cancer Risk - Ahmed, Basheer Ayyed; Kandala, Nuha J. (Iraqi Journal of Science, 2026)
In this study, the link between bacterial infection and BCL9 gene methylation was examined, which is crucial to cancer formation. Also, it examined patients' gene methylation levels for stomach ulcers, gastritis [acute and chronic], and duodenal ulcers and cancer risk. Using MS-RT-PCR, BCL-9 methylation was associated more strongly with clinical variables. Substantial differences in BCL-9 methylation between patients and controls (median 1.368, Interquartile Range [0.912-1.468] vs. 1.001, [0.861-1.211], p<0.05). Interestingly, males had substantially greater BCL-9 methylation levels than females (median 1.186, Interquartile Range [1.139-1.308] vs. 0.986, Interquartile Range [0.875-1.150], p<0.05). A significant difference was observed in BCL-9 methylation between acute and chronic gastritis patients (median 1.213, Interquartile Range [1.083-1.378] vs. 1.013, Interquartile Range [0.855-1.130], p<0.05), suggesting that chronic inflammation may impact BCL-9 methylation patterns. BCL-9 methylation was strongly linked with treatment status (r= 0.293, p<0.01). BCL-9 methylation was linked to gastrointestinal diseases such as chronic gastritis. This strongly suggests that BCL9 gene methylation can be detected early. This evidence can be utilized to create cancer treatment and prevention medicine.